RANCANG BANGUN SISTEM INFORMASI PENDATAAN BARANG PADA PT. XYZ - Monic Indah Safitri; Muhammad Yasin; Teddy Setiady (JURNAL LENTERA ICT, 2024)
The development of digital technology has significantly transformed the retail industry, necessitating a data-driven approach for companies. PT XYZ, an accessories company, currently faces challenges in its manual and inefficient product data management system. This research aims to design and develop an integrated, efficient product data collection information system. Using Unified Modeling Language (UML) as a design tool, the system incorporates three primary actors: admin, staff, and owner. The system is built using the Next.js framework. Through qualitative data collection (observations and interviews) and a literature review, this research identified key issues within the existing system: difficulty in data retrieval and inefficient business processes. The proposed information system seeks to address these challenges through automated data scanning and comprehensive report generation. It is anticipated that this system will enhance productivity, improve data accuracy, and facilitate better decision-making at PT XYZ